2020
DOI: 10.1242/jcs.228015
|View full text |Cite
|
Sign up to set email alerts
|

p63-related signaling at a glance

Abstract: ABSTRACTp63 (also known as TP63) is a transcription factor of the p53 family, along with p73. Multiple isoforms of p63 have been discovered and these have diverse functions encompassing a wide array of cell biology. p63 isoforms are implicated in lineage specification, proliferative potential, differentiation, cell death and survival, DNA damage response and metabolism. Furthermore, p63 is linked to human disease states including cancer. p63 is critical to many aspects of cell signaling, and in this Cell scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 124 publications
0
61
0
Order By: Relevance
“…Although originally thought of in terms of modifying p53 activities, it is now clear that p63 is p53‐independent, acting as a master regulator of epidermal development and with roles in mesenchymal‐derived cells and germ cell maintenance. Whilst many transcriptional targets of p63 have been identified [5–7], much less is known about how p63 is itself regulated, which is important for understanding function and for rational design and application of p63‐targeting therapeutics.…”
Section: The P53/p63/p73 Familymentioning
confidence: 99%
“…Although originally thought of in terms of modifying p53 activities, it is now clear that p63 is p53‐independent, acting as a master regulator of epidermal development and with roles in mesenchymal‐derived cells and germ cell maintenance. Whilst many transcriptional targets of p63 have been identified [5–7], much less is known about how p63 is itself regulated, which is important for understanding function and for rational design and application of p63‐targeting therapeutics.…”
Section: The P53/p63/p73 Familymentioning
confidence: 99%
“…Interestingly, we found that all mouse VDAC promoters bear specific motifs in their sequences recognized by the family of the p53 tumor suppressor transcription factors, including p63 in addition to p53. Their role in cell death, cell-cycle arrest, senescence, and metabolic regulation in response to cellular stress is well-known to affect cancer development (Chillemi et al, 2017 ; Fisher et al, 2020 ). Conservation of these TF families in mouse VDAC promoters allows us to hypothesize that the VDAC proteins are crucial in mitochondrial metabolism and in the balance of cell life and death.…”
Section: Vdac Gene Promoter and Transcription Factor Binding Sites Distributionmentioning
confidence: 99%
“…These isoforms are created by the use of two different N-terminal promotors that create either proteins containing the full-length transactivation domain (TA-isoforms) or with a truncated transactivation domain (∆N-isoforms). The different N-termini are combined with several different C-termini created by splicing events [22][23][24]. The expression of TAp63α, the longest and only expressed isoform in oocytes, increases around the time of birth, with approximately 20% of oocytes showing expression at E18.5 [25].…”
Section: Double-strand Break Checkpointmentioning
confidence: 99%